Increasing the Competitiveness of Cassava Chips MSMEs through Product Rebranding and E-Commerce Utilization in Cibeureum Hilir Village - Adinda Rifa Aurellya; Deti Mardatillah; Siti Fitriah; Arya Alamsyah; Sahrul Ramadan; Tania Yuyun Pulry; R. Edy Rachmadio; Fajar Firdausyi (Siber Nusantara Research, 2026)
This community service activity aimed to improve the competitiveness of cassava chips MSMEs in Cibeureum Hilir Village through product rebranding and utilization of e-commerce based on digital marketing. The problems faced by partners inclueded simple product packaging, unattractive brand identity, and convetional marketing methods. The implementation method used the Asset-Based Community Development (ABCD) and Participatory Action Research (PAR) approaches through observation, training, mentoring, implementation, monitoring, and evaluation stages. The programs carried out inclueded creating new logos and packaging designs, digital marketing training, marketplace utilization, and business location registration on Google Maps. The results showed improvements in product visual quality, stroger brand identity, and increased partner understanding in using digital media for marketing purposes. Product began to be promoted through marketplace and social media, helping expand market reach. In addition, registering the business location on Google Maps made it easier for consumers to find MSME. Therefore, the implementation of rebranding strategies and e-commerce optimization ws considered effective in improving MSME competitiveness sustainably